A homozygous SLITRK6 nonsense mutation is associated with progressive auditory neuropathy in humans. (17th December 2013) - Morlet, Thierry; Rabinowitz, Mindy R.; Looney, Liesl R.; Riegner, Tammy; Greenwood, L. Ashleigh; Sherman, Eric A.; Achilly, Nathan; Zhu, Anni; Yoo, Estelle; O'Reilly, Robert C.; Jinks, Robert N.; Puffenberger, Erik G.; et al.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis SLITRK family proteins control neurite outgrowth and regulate synaptic development. In mice, Slitrk6 plays a role in the survival and innervation of sensory neurons in the inner ear, vestibular apparatus, and retina, and also influences axial eye length. We provide the first detailed description of the auditory phenotype in humans with recessive SLITRK6 deficiency. Study Design Prospective observational case study. Methods Nine closely related Amish subjects from an endogamous Amish community of Pennsylvania underwent audiologic and vestibular testing. Single nucleotide polymorphism microarrays were used to map the chromosome locus, and Sanger sequencing or high‐resolution melt analysis were used to confirm the allelic variant. Results All nine subjects were homozygous for a novel nonsense variant of SLITRK6 (c.1240C>T, p.Gln414Ter). Adult patients had high myopia. The 4 oldest SLITRK6 c.1240C>T homozygotes had absent ipsilateral middle ear muscle reflexes (MEMRs). Distortion product otoacoustic emissions (DPOAEs) were absent in all ears tested and the cochlear microphonic (CM) was increased in amplitude and duration in young patients and absent in the two oldest subjects. Auditory brainstem responses (ABRs) were dys‐synchronised bilaterally with no reproducible waves I, III, or V at high intensities. Hearing loss and speech reception thresholds deteriorated symmetrically with age, which resulted in severe‐to‐profound hearing impairment by early adulthood. Vestibular evoked myogenic potentials were normal in three ears and absent in one. Conclusion Homozygous SLITRK6 c.1240C>T (p.Gln414Ter) nonsense mutations are associated with high myopia, cochlear dysfunction attributed to outer hair cell disease, and progressive auditory neuropathy. Level of Evidence N/A. Laryngoscope, 124:E95–E103, 2014